Sakpada-Pada: Jalan Tengah Kesetaraan Di Pedesaan Jawa, 1850 – 2010 (Jurnal Kawistara, 2020)
This study discusses the praxis of human equality among mountains farming communities inPetungkriyono Subdistrict, Pekalongan, Central Java, through long-term historical-ethnographic observations on local political and economic activities in village head election and livestock raising. Village communities are always divided by hierarchical social structures between ordinary citizens and the elite. From time to time the elite and the rich continue to face social-economic guerrilla from ordinary citizens and social-economic competition from their peers. The interest of villagers is not to erase hierarchical structures but rather to stem elite pressure, while at the same time maintaining hopes, ideals and striving to experience increased social mobility, becoming residents of the upper social layers in society. In more straight forward language, they do not move to erase the differences between rich and poor but aspire and work to become rich. These ideals are built on the ideology of human equality that humans have the same right to live regardless of poor or rich, elite or villagers.